2021
DOI: 10.1101/2021.02.09.430411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Streptococcus pyogenesforms serotype and local environment-dependent inter-species protein complexes

Abstract: Streptococcus pyogenes is known to cause both mucosal and systemic infections in humans. In this study, we used a combination of quantitative and structural mass spectrometry techniques to determine the composition and structure of the interaction network formed between human plasma proteins and the surface of different S. pyogenes serotypes. Quantitative network analysis revealed that S. pyogenes form serotype-specific interaction networks that are highly dependent on the domain arrangement of the surface-att… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 69 publications
0
4
0
Order By: Relevance
“…The serotypes that do not bind fibrinogen via the M protein might acquire fibrinogen to the surface via another surface protein in the M-related protein family ( 12 ). Recent work has shown that the emm 28, -49, and -89 bacterial serotypes from pattern E also bind significantly less fibrinogen to the bacterial surface than the emm 1, -3, and -5 serotypes ( 39 ) from pattern A-C. Distinct human plasma-interactome networks were observed for the serotypes from pattern A-C that acquired mainly fibrinogen and complement proteins, while pattern E serotypes acquired mainly apolipoproteins, immunoglobulins, and coagulation proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The serotypes that do not bind fibrinogen via the M protein might acquire fibrinogen to the surface via another surface protein in the M-related protein family ( 12 ). Recent work has shown that the emm 28, -49, and -89 bacterial serotypes from pattern E also bind significantly less fibrinogen to the bacterial surface than the emm 1, -3, and -5 serotypes ( 39 ) from pattern A-C. Distinct human plasma-interactome networks were observed for the serotypes from pattern A-C that acquired mainly fibrinogen and complement proteins, while pattern E serotypes acquired mainly apolipoproteins, immunoglobulins, and coagulation proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The cloning, expression, and purification of the recombinant proteins used in this study have been described previously ( 39 ). For this study, the proteins were further purified using StrepTactin Sepharose (Sigma-Aldrich), washed with phosphate-buffered saline (PBS), and eluted with 5 mM biotin in PBS (Sigma-Aldrich).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations